Pengaruh Kepuasan Kerja terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kecamatan Sungai Tarab dan Salimpaung - Baiyulis Baiyulis; Syamsir Syamsir; Jumiati Jumiati (Faculty of Social Science, Universitas Negeri Padang, 2018)
The purpose of this study was to analyze the effect of job satisfaction on the performance of nagari apparatus in nagari financial management in Sungai Tarab and Salimpaung Subdistricts, Tanah Datar Regency. This study was a quantitative research with associative method. The population of this study was all nagari apparatus in the two subdistricts, Sungai Tarab and Salimpaung, which numbered 112 people. Sampling in this study used the Slovin formula and consisted of 79 nagari apparatus. Besides, sample in this study determined through proportional random technique. Data in this study were collected through questionnaires with Likert scale measurement distributed to respondents. The data obtained were then analyzed using multiple linear regression. The results of this study indicated that salaries, the work itself, co-workers, supervision, promotion and work environment, together and partially, had a significant effect on the performance of nagari apparatus in managing nagari financial in the two subdistricts. So that it could be concluded that the job satisfaction of nagari apparatus had a significant effect on the performance of nagari apparatus in nagari financial management in Sungai Tarab and Salimpaung Subdistricts, Tanah Datar Regency.